205 Optimization of DBS Electrode Position With Multisite Microelectrode Recordings, Macrostimulation, and Atlas-Based Prediction Maps Visualized in 3D. (1st April 2022) - Paulo, Danika L.; Narasimhan, Saramati; Gonzalez, Hernan F. J.; Rodriguez, William; Li, Rui; Konrad, Peter; Neimat, Joseph S.; Shah, Hamid M.; Bick, Sarah K. B.; D'Haese, Pierre; Dawant, Benoit M.; Englot, Dario J.
Abstract : INTRODUCTION: Deep brain stimulation (DBS) at our institution is performed with a custom-made miniature stereotactic frame (STarFix, FHC) with the patient kept awake during electrode implantation to perform microelectrode recordings (MER) and macrostimulation testing. Pre-operative targets are selected with guidance from atlas-based efficacy prediction maps. Multisite intraoperative microelectrode recordings (MER) and macrostimulation data are collected, visualized in 3D in real-time, and integrated into selection of a final target. METHODS: A sample of 490 patients treated with DBS at Vanderbilt from 2011-2021 with 892 individual leads were included. During surgery, FHC microelectrodes are implanted in 2-3 test tracks on each side and microelectrode recordings are collected. Atlas-based prediction maps based on position and efficacy of previous cases help guide targeting. Macrostimulation data is collected at multiple depths along the same tracks, with efficacy quantified in quartiles and side effects noted. Preoperative maps and intraoperative data are visualized in 3D with color and integrated in real time to guide optimal FEP selection. Basic statistics were used to calculate percentages and means. RESULTS: Of 892 individual leads, 467 (52%) had FEP in the center track and 225 of those had FEP within 1mm of planned target depth. MER was collected in 435 (49%) of test tracks with 380 (43%) recordings collected in the FEP track. Stimulation data was collected for all leads and 867 (97%) of FEP tracks. CONCLUSION: Although planned targets were carefully selected preoperatively based on anatomy, coordinates, and guidance from atlas-based efficacy maps, FEP differed from anticipated target in 75% of cases. This discrepancy supports use of multisite MER and stimulation testing and the value of keeping patients awake to complete testing, optimizing their FEP in real-time based on maximal efficacy and minimal side effects. Finally, atlas-based prediction maps help guide initial targeting.